Lithofacies and Grain-size Analysis of the Oligocene Nari Formation, Benir Anticline, Southern Indus Basin, Pakistan: Evidence of a Marine-to-Continental Depositional Shift - Hakro, Asghar A. A. D.; Halepoto, Aijaz Ali; Ahmedani, Surriya Bibi; Bhutto, Abdul Samad; Abdul Shakoor Mastoi (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2025)
In the Southern Indus Basin, Pakistan, the Nari Formation of Oligocene age represents an important stratigraphic unit that preserves a classical regressive depositional sequence, recording a significant transition from marine to continental environments. This study analyzes the lithofacies and grain-size parameters of the Nari Formation from the Benir anticline section, Southern Indus Basin, to interpret its depositional environments. A 65 m thick stratigraphic section was measured and divided into non-clastic and clastic lithofacies groups. Non-clastic lithofacies group observed in the lower part of the Nari Formation and consists of compacted limestone, coquinoidal limestone and arenaceous limestone lithofacies, indicating deeper outer-ramp to near-shore depositional environments. The clastic lithofacies group was identified in the upper part, which consists of calcareous sandstone, variegated and gypsiferous shale, lateritic sandstone and friable sandstone lithofacies, suggesting continental fluvial depositional conditions. Shale-bearing lithofacies were identified in the middle part of the Nari Formation, reflect evaporitic and oxidizing continental settings. Grain-size analysis of eleven samples from friable sandstone facies supports a river-dominated origin. The vertical transition from marine to continental facies in the Nari Formation reflects a significant depositional shift, documenting a regressive sequence from marine ramp to fluvial settings. This study contributes to the broader understanding of the stratigraphic evolution of the Southern Indus Basin in relation to Oligocene regional tectonic background.